An Empirical Study on the Factors Affecting the Layout of the Dairy Industry - Based on China’s Provincial Panel Data Analysis - Jia, Shushuai (Asia Social Issues, 2023)
The dairy industry is an essential civilian production industry. The study aims to explore the main factors that affect the layout of the dairy industry and determine the extent of the impact of industrial scale, industrial technology, and industrial resources on the industrial layout. Based on statistical data on China’s dairy industry, this paper mainly focuses on how the industrial scale, resources, and supportive policies towards the dairy industry distribution. The results show that the three of them significantly impact industrial distribution; meanwhile, the impacts of industrial policy on industrial distribution are performed more comprehensively. Then the paper discusses the influence and transmission mechanisms and provides recommendations to improve China’s dairy industry layout.